Experts' and Patients' Views About Pain on Swallowing: A Qualitative Study - fatemeh Kiaee Darounkola; masoomeh salmani; Seyed Abolfazl Tohidast; Jalal Bakhtiyari (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Swallowing disorder or dysphagia is one of the most common problems in old age and after brain vascular lesions. This problem has received a lot of attention in studies. However, Pain on swallowing (known as odynophagia) has been less discussed in the literature. The present study aimed to investigate the existence of pain on swallowing, its characteristics, the possible intervention, and the effects of this pain on the quality of life of affected people. Materials & Methods The present study adopted a qualitative approach. After purposeful sampling, we interviewed 11 speech therapists in the field of swallowing disorders (5 males) and 15 patients with dysphagia. All the interviews were transcribed and underwent content analysis using the Graneheim and Lundman method. Finally, the main themes, subcategories, semantic units, and examples related to each were obtained. Results Out of 15 interviewed patients, only 6 reported pain on swallowing. In comparison, all 11 therapists in the field of swallowing disorders confirmed the presence of pain on swallowing. Seven main themes were obtained based on these interviews: The temporal pattern, duration, location, stimulating/provoking factors, type, intensity, and onset time. Each of these themes had its subcategories and items. All patients and therapists reported the negative impact of pain on swallowing on the quality of life. There was an agreement between therapists and patients to manage pain on swallowing. Conclusion This study showed that pain on swallowing is probably one of the characteristics of a swallowing disorder, and professionals must consider pain on swallowing during the clinical examination. Future studies can focus on different dimensions of pain on swallowing and develop proper evaluation scales.